TOURQUAL: Proposal of a Protocol For Quality Evaluation on Services at Tourist Attractions - Tiago Savi Mondo; Gabriela Gonçalves Silveira Fiates (BBR: Brazilian Business Review)
Tourism has been an important economic activity worldwide in recent years, and the increasing number of tourists and the competition among destinations pressure for the highest quality possible for tourists. The objective of this research is to propose a model to analyze the quality of services at tourist attractions. The first stage consisted of two bibliometric researches being performed, in order to identify the ‘state of art’ and verify the existing models of quality evaluation. Identified 36 models and 211 indicators of quality. From this initial exploratory research, a preliminary theoretical model was designed which worked with 35 indicators. The second stage collected and analyzed comments left by tourists on TripAdvisor.com. Analyzed 68.301 comments about tourist attractions in eight Brazilian cities, using the software T-LAB and compared with the indicators in the preliminary theoretic model. After of 35 indicators, 23 were maintained, 12 were excluded, and three new theoretic indicators were created, which made it possible to build a model able to be empirically tested. The test was carried out with 476 tourists who evaluated tourist attractions in Florianópolis-Brazil. In the confidence and questionnaire validation test the Alpha Conbranch presented an excellent result of 0.904 confirming the proposed model.